Pengaruh Asas Netralitas Birokrasi dalam Pemilukada terhadap Efektifitas Kinerja Aparatur Sipil Negara di Kota Banjar Jawa Barat Tahun 2019 - Syaeful Bachri; Irma Bastaman; Nurdiana Mulyantini (Jurnal Manajemen Bisnis Era Digital, 2024)
The problems faced in this study include (1) How is the principle of bureaucratic neutrality in the regional elections in Banjar City, West Java in 2019? (2) How is the effectiveness of the performance of state civil servants in Banjar City, West Java in 2019? (3) How does bureaucratic neutrality in regional elections affect the effectiveness of state civil servant performance in Banjar City, West Java in 2019? This study aims to study, find out, and analyze (1) The principle of bureaucratic neutrality in regional elections in Banjar City, West Java in 2019. (2) The effectiveness of state civil servant performance in Banjar City, West Java in 2019? (3) the effect of the principle of bureaucratic neutrality in regional elections on the effectiveness of state civil servant performance in Banjar City, West Java in 2019. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Simple Linear Regression (Simple Regression). The results of the study inform that (1) The principle of bureaucratic neutrality in the regional elections in Banjar City, West Java in 2019 has not been optimal, but after the study was conducted, it tends to be very high. The highest value is on the impartial indicator and the lowest value is on the not involved indicator. (2) The effectiveness of the performance of the State Civil Apparatus in Banjar City, West Java in 2019 has not been optimal, but after the study was conducted, it tends to be very high. The highest value is on the outcome measurement indicator and the lowest value is on the time measurement indicator. (3) The principle of bureaucratic neutrality in the regional elections has a positive effect on the effectiveness of the performance of the State Civil Apparatus in Banjar City, West Java in 2019.